Vapautumisen estetiikka : Eino Krohn taiteen ja kirjallisuuden tutkijana - Ammondt, Jukka (1991)
Eino Krohn (1902 - 1987) is one of the most remarkable Finnish aestheticians and critics of art. His numerous academic works include aesthetic and theoretical treatises as well as studies in literature and drama.